Implementation of General Election Commission Regulation (PKPU) Number 7 of 2024 in Bitung City - Hamisi, Wiwinda; Bogar, Wilson; Kairupan, Sisca Beatrix (International Journal of Information Technology and Education, 2025)
This study aims to analyze the implementation of the General Election Commission Regulation (PKPU) Number 7 of 2024 concerning the Compilation of the Voter List in Bitung City. The research focuses on the effectiveness of policy socialization, the capacity of election organizers, and the influence of local socio-political conditions on the success of the policy implementation. A descriptive qualitative method with a case study approach was employed, with data collected through in-depth interviews with key informants such as the Chairperson of the Bitung City KPU, the Commissioner of the Data Planning and Information Division, the KPU Secretary, the Head of the Department of Population and Civil Registration (Dukcapil), and a Commissioner of Bawaslu. The findings indicate that the implementation of PKPU Number 7 of 2024 has been effective through the formation of Voter Data Updating Teams (TPDP) at various levels, inter-agency coordination, and the use of technology such as the Socialization and Data Updating System (SSPD). Policy socialization was conducted through various methods, including focus group discussions (FGDs), digital media, and door-to-door approaches, which successfully improved public understanding and participation in data verification. Major challenges include difficult geographical conditions, varying levels of digital literacy, and the need for adequate logistical resources. Nevertheless, collaborative efforts between KPU, Dukcapil, and Bawaslu have succeeded in reducing data errors from 4.2% to 1.8% and improving the accuracy of the Final Voter List (DPT).